2004
DOI: 10.1016/j.ejvs.2004.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-Traumatic Lower Limb Vascular Complications in Endurance Athletes. Review of Literature

Abstract: Non-traumatic vascular complications affecting the lower limbs include endofibrosis, stenosis/kinking of iliac arteries, dissection of external iliac artery, adductor canal syndrome, popliteal entrapment syndrome, chronic exertional compartment syndrome and effort-induced venous thrombosis. These are important as they affect athletes at the peak of their career and can be confusing to diagnose. The management is relatively well documented and produces good results in short term but the long term results are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 63 publications
(116 reference statements)
2
35
0
Order By: Relevance
“…It has been reported that non-traumatic vascular complications (including stenosis) in athletes may lead to impaired performance [7]. Our results did not indicate any difference in maximal strength nor endurance between subjects with and without an AA.…”
Section: Discussionsupporting
confidence: 30%
“…It has been reported that non-traumatic vascular complications (including stenosis) in athletes may lead to impaired performance [7]. Our results did not indicate any difference in maximal strength nor endurance between subjects with and without an AA.…”
Section: Discussionsupporting
confidence: 30%
“…56 A frequent cause of PAES is compression of the popliteal artery by surrounding musculotendinous structures as it exits the popliteal fossa; the most common variant involves an accessory medial head of the gastrocnemius passing posterior to the popliteal artery. 6,13,20 Popliteal compression can also be caused by fibrous bands of the gastrocnemius or the popliteus muscle or an aberrant course of the popliteal artery. 20 PAES can also be functional, with vascular testing results often normal.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…6,13,20 Popliteal compression can also be caused by fibrous bands of the gastrocnemius or the popliteus muscle or an aberrant course of the popliteal artery. 20 PAES can also be functional, with vascular testing results often normal. 56 …”
Section: Differential Diagnosismentioning
confidence: 99%
“…This disorder primarily effects young, healthy, physically active patients and was initially described by Eduardo Palma in early 1950′s [1], [2], [3]. The pathophysiology of this condition involves chronic external compression of the superficial femoral artery within the adductor canal that ultimately leads to vessel injury, in-situ thrombosis, limb ischemia and potential limb loss [4], [5], [6]. The precise source of the external compression varies from case-to-case but published reports have described “embryologic” fibrous bands [5], [7], an anomalous musculotendinous band arising from the adductor magnus muscle [4] and hypertrophied adductor magnus or vastus medialis muscles [8].…”
Section: Introductionmentioning
confidence: 99%